Special physical training of acrobats taking into account the requirements of the selected amploice (on the example of the bottom partners) - Denisenko, Vladislava (Journal of Education, Health and Sport, 2020)
The article presents the results of introducing the program of special physical training of bottom acrobats into the training process, taking into account the requirements of the chosen position at the stage of preliminary basic training. The data obtained showed that the use of this program allows bottom acrobats to more successfully and qualitatively master the necessary skills of pair work, and also increases the response of partners as a system of bodies, which is confirmed by stabilographic studies.